2012
DOI: 10.1038/ejhg.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Variable imprinting of the MEST gene in human preimplantation embryos

Abstract: There is evidence that expression and methylation of the imprinted paternally expressed gene 1/mesoderm-specific transcript homologue (PEG1/MEST) gene may be affected by assisted reproductive technologies (ARTs) and infertility. In this study, we sought to assess the imprinting status of the MEST gene in a large cohort of in vitro-derived human preimplantation embryos, in order to characterise potentially adverse effects of ART and infertility on this locus in early human development. Embryonic genomic DNA fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…For the amplification of the MEST-1C sequences, the PCR conditions and primer sequences are listed in Table S1. The PCR products were purified and subjected to BSP (10 positive clones) and Combined Bisulfite Restriction Analysis (COBRA) (Huntriss et al, 2013;Watanabe et al, 2010).…”
Section: Methylation Pattern Of Mest-1c Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the amplification of the MEST-1C sequences, the PCR conditions and primer sequences are listed in Table S1. The PCR products were purified and subjected to BSP (10 positive clones) and Combined Bisulfite Restriction Analysis (COBRA) (Huntriss et al, 2013;Watanabe et al, 2010).…”
Section: Methylation Pattern Of Mest-1c Sequencesmentioning
confidence: 99%
“…Multiple transcript isoforms of MEST have been identified as being imprinted in a tissue-and isoform-specific manner in humans and mice (Kosaki et al, 2000;Huntriss et al, 2013;Kamei et al, 2007), while there are no reports that MEST is isoform-specific imprinted in pigs. With this background, we are interested in identifying the imprinting status of porcine MEST isoforms by quantitative real-time PCR (qRT-PCR) and bisulfite sequencing PCR analysis (BSP) using parthenogenetic fetuses as a model.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of expression of this long non-coding RNA correlates with biallelic expression ('loss of imprinting') of IGF2R and of close-by placenta-specific genes (Monk et al, 2006). The growth-related PEG1/MEST gene on human chromosome 7q32 is polymorphically imprinted (Huntriss et al, 2013); its isoform-2 in placenta and early embryos is highly variable between conceptuses and this correlates with differential DNA methylation levels at an exonic differentially methylated region (McMinn et al, 2006).…”
Section: Genetic Polymorphisms and The Control Of Mono-allelic Gene Ementioning
confidence: 99%
“…Mesoderm-specific transcript (MEST) is expressed in the paternal allele and encodes a alpha/beta hydrolase fold family enzyme with unknown function, which is located on proximal chromosome 6 in mice and chromosome 7q32 in humans (Huntriss et al, 2013). This gene is highly expressed in the early stage embryo, specifically in the mesodermal tissue (Kobayashi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that assisted reproductive technology influences DNA methylation and expression of MEST in humans and mice. It has been reported that hyper methylation of the MEST gene in differentially methylated region leads to Silver-Russel syndrome, which is thought to be caused by IVF (Huntriss et al, 2013;Imamura et al, 2005).…”
Section: Introductionmentioning
confidence: 99%